2020
DOI: 10.3390/agronomy10010095
|View full text |Cite
|
Sign up to set email alerts
|

Is Phytomelatonin a New Plant Hormone?

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is of particular importance as a chronobiological hormone in mammals, acting as a signal of darkness that provides information to the brain and peripheral organs. It is an endogenous synchronizer for both endocrine (i.e., via neurotransmitter release) and other physiological rhythms. In this work we will try to add to the series of scientific events and discoveries made in plants that, surprisingly, confirm the great similarity of action of melatonin in animals and plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 121 publications
1
61
0
1
Order By: Relevance
“…[20][21][22] Recently, we identified the first phytomelatonin receptor (PMTR1, previously named CAND2) that regulates stomatal closure via NADPH oxidase-dependent ROS signaling pathway in Arabidopsis, 10 suggesting a possibility that this molecule is a new plant hormone. 10,19,23 Although it has been shown that the endogenous concentrations of phytomelatonin peak during darkness in Chenopodium rubrum as in vertebrates, 24,25 these observations were challenged lately as several publications found that the biosynthesis of melatonin is induced by light but decreased under darkness conditions in morning glory, 26 Arabidopsis 27 and rice. 28 Therefore, it remains controversial whether this newly characterized putative phytohormone is involved in regulation of daily rhythms as the endogenous concentrations of phytomelatonin are always affected by plant growth conditions and environmental factors (eg, temperature, UV light, and water status ).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Recently, we identified the first phytomelatonin receptor (PMTR1, previously named CAND2) that regulates stomatal closure via NADPH oxidase-dependent ROS signaling pathway in Arabidopsis, 10 suggesting a possibility that this molecule is a new plant hormone. 10,19,23 Although it has been shown that the endogenous concentrations of phytomelatonin peak during darkness in Chenopodium rubrum as in vertebrates, 24,25 these observations were challenged lately as several publications found that the biosynthesis of melatonin is induced by light but decreased under darkness conditions in morning glory, 26 Arabidopsis 27 and rice. 28 Therefore, it remains controversial whether this newly characterized putative phytohormone is involved in regulation of daily rhythms as the endogenous concentrations of phytomelatonin are always affected by plant growth conditions and environmental factors (eg, temperature, UV light, and water status ).…”
Section: Introductionmentioning
confidence: 99%
“…Drought might lead to excessive generation of reactive oxygen species (ROS), which can cause oxidative damage to photosynthetic components [19]. The antioxidant enzymes were crucial for controlling excessive levels of ROS, and some plant growth regulators, such as melatonin, were used to improve the antioxidant enzyme activity and scavenge ROS under drought [20,21].Maize is an important food and feed crop around the world and is also widely used in industrial products. The effects of drought on maize have been extensively investigated.…”
mentioning
confidence: 99%
“…Arnao et al, (2020) have reviewed extensively the importance of phytomelatonin. 38 To this end, the application of exogenous MLN could potentially trigger these responses. Exogenous MLN upregulates the antioxidant system of plants to protect them against reactive oxygen species.…”
Section: Reaction Kinetics Of Agnps Biosynthesismentioning
confidence: 99%